2015
DOI: 10.5194/sed-7-2011-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of soil depth on the dynamics of selected soil properties among the highlands resources of Northeast Wollega, Ethiopia: are these sign of degradation?

Abstract: Abstract. This study was conducted with an aim to analyze the spatial variability of soil properties with depth under four prominent land use patterns viz., forestland, grazing land, cultivated land and bush land of Northeast Wollega. Soil samples were collected from the land uses at two depths (0–15 and 15–30 cm) in replicates and totally 40 composite soil samples were collected. Statistical analysis revealed significant variation in soil properties with along the selected land uses. Topsoil layer had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…This finding is in accordance with (Adugna & Abegaz, 2015;Negasa, 2020). Even though, the fact that the measured pH values in both natural bamboo forest and cultivated land uses of the subsurface lie within the optimal ranges (6-7.5), we observed that deforestation and subsequent cultivation can lead to rise in soil pH (Table 4).…”
Section: Soil Ph Soil Organic Carbon and Total N Contentssupporting
confidence: 88%
“…This finding is in accordance with (Adugna & Abegaz, 2015;Negasa, 2020). Even though, the fact that the measured pH values in both natural bamboo forest and cultivated land uses of the subsurface lie within the optimal ranges (6-7.5), we observed that deforestation and subsequent cultivation can lead to rise in soil pH (Table 4).…”
Section: Soil Ph Soil Organic Carbon and Total N Contentssupporting
confidence: 88%
“…The clay and SOM contents influence the CEC of the soils (Soares and Alleoni, 2008;Adugna and Abegaz, 2015;Nesic et al, 2015), a contrary fact was observed by Saidian et al (2016), who reported that CEC values were related to the clay type (smectite versus kaolinite) present in the soil and were independent of the SOM content and its degree of decomposition (Chapman, 1965;Sumner and Miller, 1996). Hobley and Wilson (2016) reported that carbon content is influenced by land use and climatic factors.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Elissa and Harry () also observed poor relationship between CEC and clay. Further, many researchers observed deviation from the usual high correlation between CEC and clay and attributed it to intensity of cultivation (Shrestha, Singh, Sitaula, Lal, & Bhattacharyya, ); variation in soil depth (Adugna & Abegaz, ; He, Wu, Wang, & Han, ) and structure and type of clay minerals (Vogel et al, ; Yang, Drury, Reynolds, & Yang, ).…”
Section: Resultsmentioning
confidence: 99%